Magnetically confined fusion plasma physics. - Zheng, Linjin (IOP (Series). Release 22., 2022)
This is the third volume in a set of books describing state-of-the-art theories and applications of magnetically confined fusion plasmas. This volume presents advanced kinetic theory, aiming to fill the gap between plasma physics textbooks and up-to-date research developments in this field.